Inactivation of the Euchromatic Histone-Lysine N-Methyltransferase 2 Pathway in Pancreatic Epithelial Cells Antagonizes Cancer Initiation and Pancreatitis-Associated Promotion by Altering Growth and Immune Gene Expression Networks - Urrutia, Guillermo; de Assuncao, Thiago Milech; Mathison, Angela J.; Salmonson, Ann; Kerketta, Romica; Zeighami, Atefeh; Stodola, Timothy J.; Adsay, Volkan; Pehlivanoglu, Burcin; Dwinell, Michael B.; Zimmermann, Michael T.; Iovanna, Juan L.; et al. (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is an aggressive, painful disease with a 5-year survival rate of only 9%. Recent evidence indicates that distinct epigenomic landscapes underlie PDAC progression, identifying the H3K9me pathway as important to its pathobiology. Here, we delineate the role of Euchromatic Histone-lysine N-Methyltransferase 2 (EHMT2), the enzyme that generates H3K9me, as a downstream effector of oncogenic KRAS during PDAC initiation and pancreatitis-associated promotion. EHMT2 inactivation in pancreatic cells reduces H3K9me2 and antagonizes KrasG12D-mediated acinar-to-ductal metaplasia (ADM) and PanIN formation in both the Pdx1-Cre and P48+/-Cre KrasG12D mouse models. Ex vivo acinar explants also show impaired EGFR-KRAS-MAPK pathway-mediated ADM upon EHMT2 deletion. Notably, KrasG12D increases EHMT2 protein levels and EHMT2-EHMT1-WIZ complex formation. Transcriptome analysis reveals that EHMT2 inactivation upregulates a cell cycle inhibitory gene expression network that converges on the Cdkn1a/p21-Chek2 pathway. Congruently, pancreas tissue from KrasG12D animals with EHMT2 inactivation have increased P21 protein levels and enhanced senescence. Furthermore, loss of EHMT2 reduces inflammatory cell infiltration typically induced during KrasG12D-mediated initiation. The inhibitory effect on KrasG12D-induced growth is maintained in the pancreatitis-accelerated model, while simultaneously modifying immunoregulatory gene networks that also contribute to carcinogenesis. This study outlines the existence of a novel KRAS-EHMT2 pathway that is critical for mediating the growth-promoting and immunoregulatory effects of this oncogene in vivo, extending human observations to support a pathophysiological role for the H3K9me pathway in PDAC.